Chaotic pulse position modulation ultra-wideband system based on particle filtering - 李辉 Zhang Li (高技术通讯（英文版）, 2013)
Traditional chaotic pulse position modulation （CPPM） system has many drawbacks. It intro- duces delay into the feedback loop, which will lead to divergence of chaotic map easily. The wrong decision of data will cause error propagation. Mismatch of parameters and synchronization error between the receiver and transmitter will arouse high bit error rate. To solve these problems, a demodulation algorithm of CPPM based on particle filtering is proposed. According to the mathematical model of the system, it tracks the real signal by online separation in demodulation. Simulation results show that the proposed method can track the true signal better than the traditional CPPM scheme. What＇ s more, it has good synchronization robustness, reduced error propagation by wrong decision and low bit error rate.